A rare case of hereditary sensory and autonomic neuropathy type II - Elmira Mamytova; Asel Jusupova; Anara Toktomametova; Kunduz Karbozova; Begimay Kadyrova; Yethindra Vityala; Tugolbai Tagaev (Clinical Case Reports, 2023)
Abstract We describe the follow‐up of a 29‐year‐old man diagnosed with hereditary sensory and autonomic neuropathy type II, including the different complications that presented since his childhood. Despite efforts to maintain an optimal quality of life, the lack of an early diagnosis led to an unfavorable prognosis and life condition.